DESKRIPSI DAN KORELASI ANTARA PENGETAHUAN DENGAN PERILAKU KONSUMEN MINUMAN FERMENTASI - Rasmikayati, Elly; Wiyono, Sulistyodewi Nur; Saefudin, Bobby Rachmat (Jurnal Pertanian Agros, 2025)
Fermented drinks are healthy drinks that play an important role in culture and tradition in Indonesia. Drinks that have health benefits have become a trend due to increasing public awareness of health. However, there is limited public knowledge about fermented beverage products which have an important role in shaping a person's consumption behavior. This study aims to describe and analyze the correlation between knowledge and behavior of fermented beverage consumer. The research method uses a survey method to 56 fermented drink consumers from the results of simple random sampling techniques. Data analysis uses descriptive statistics and chi square tests. The results of the study include showing a significant correlation between knowledge of the benefits of fermented beverage, knowledge of many types of fermented beverage, and knowledge of the lack of fermentation in consumer knowledge variables with reasons for consuming fermented beverage and many brands of fermented beverage consumed in consumption behavior variables.